If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 5x Reorder the terms: 6 + 3x = 5x Solving 6 + 3x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 3x + -5x = 5x + -5x Combine like terms: 3x + -5x = -2x 6 + -2x = 5x + -5x Combine like terms: 5x + -5x = 0 6 + -2x = 0 Add '-6' to each side of the equation. 6 + -6 + -2x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 0 + -6 -2x = 0 + -6 Combine like terms: 0 + -6 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 8c-4=2-4c | | (x+2)(2x+1)=(x+6)(2x+3) | | 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 | | 8+13=-3(7x-7) | | 5(5t-2)=-36 | | 9x+1=46 | | -4(y-3)=6y-7 | | m/6=-9 | | .5x+1.25y=.5 | | n+15=23 | | 8+13=3(7x-7) | | -(3x-5y)-8(2x+y)= | | -2.35+6.75=-2.18 | | (a^3b)(ab^3)= | | 0.667(6x-15)=0.75(8x+12) | | 5r-13-6r=3(r+5)-16 | | x+15=0 |